2019
DOI: 10.1021/acs.jchemed.9b00396
|View full text |Cite
|
Sign up to set email alerts
|

Michaelis–Menten Graphs, Lineweaver–Burk Plots, and Reaction Schemes: Investigating Introductory Biochemistry Students’ Conceptions of Representations in Enzyme Kinetics

Abstract: This work seeks to add to the growing body of chemistry education research that emphasizes the teaching and learning of advanced topics, focusing on students' understanding of enzyme kinetics. The data corpus relevant to this study involved 14 second-year undergraduate students enrolled in an introductory biochemistry course taught in a chemistry department. During semistructured interviews, the students were prompted to discuss a typical enzyme kinetics reaction scheme (i.e., E + S ⇌ ES → E + P) and describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 78 publications
0
26
0
Order By: Relevance
“…Finally, the apparent Michaelis–Menten ( ) constant was calculated following the Lineweaver–Burk approach by representing 1/I lim vs. 1/[S ox ], where I lim is the intensity of the maximum and Sox is the substrate concentration (catechol in this case) [ 46 ]. These results confirm the excellent performance of AgNWs as electron mediators, probably due to the excellent affinity between the AgNWs and the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the apparent Michaelis–Menten ( ) constant was calculated following the Lineweaver–Burk approach by representing 1/I lim vs. 1/[S ox ], where I lim is the intensity of the maximum and Sox is the substrate concentration (catechol in this case) [ 46 ]. These results confirm the excellent performance of AgNWs as electron mediators, probably due to the excellent affinity between the AgNWs and the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the data were necessary to provide insight regarding how students attended to the axes. Previous work related to chemical kinetics indicates students often overlook the relationship between the axes and the system being modeled, ,, thus, it could be that when students are prompted to draw a rate vs time graph they are thinking about a different related graph (e.g., concentration vs time ). By asking students to draw multiple graphs contextualized within the same scenario, we are forcing students to attend to the feature that is changing ( y -axis) and reason about its implications.…”
Section: Resultsmentioning
confidence: 99%
“…Prior research has shown that students have difficulty discussing the concept of reaction rate, often conflating chemical kinetics with equilibrium , , rate with time, ,, or rate with rate constant . Furthermore, for advanced chemistry topics that build on chemical kinetics, such as enzyme kinetics, other challenges have been reported related to vocabulary, as well as the use of representations such as graphs and equations. ,, In this study, we focus on students’ reasoning related to reaction rate, in which students constructed a graphical model to describe how reaction rate changes over time. Here, we view student-drawn graphs as models, in which the specific shapes of the graphs can be used to explain what is happening within the target system.…”
mentioning
confidence: 99%
“…In the final paper published for this project, themes were discussed related to how students described the Michaelis-Menten graph, Lineweaver-Burk plot, and reaction scheme (i.e., E þ S ES E þ P) (70). With respect to the Michaelis-Menten graphs, it was noted that 4 of the students in the sample implicitly or explicitly attributed time to the x-axis, with similar results discussed in other research related to students' understanding of reaction coordinate diagrams (17).…”
Section: Investigating Student Understanding Of Representations Inmentioning
confidence: 99%
“…Building on our recent work in chemical kinetics that emphasized students' mathematical reasoning during problem solving (7,16,60,(64)(65)(66)-tersely summarized in a recent book chapter (67)-here, we focus on students' understanding of enzyme kinetics, guided by the overarching research question: How do students reason about enzyme kinetics? Addressing this question involves a brief overview of the themes that emerged from our enzyme kinetics project, which focused on students' mathematical reasoning related to rate laws and reaction order (68), student conceptions of enzyme inhibition and the associated mechanisms (69), and student understanding of representations such as Michaelis-Menten graphs, Lineweaver-Burk plots, and reaction schemes (70). After providing an overview of the results, we focus on the implications this work has for improving the teaching and learning of chemistry, using the refined consensus model of pedagogical content knowledge to frame the results for practitioners.…”
Section: Introductionmentioning
confidence: 99%